Neighbourhood participation and social inclusion: Case studies of Calgary, Alberta. Issue 132 (June 2022) - Benoit, Aimee; Townshend, Ivan J.; Johnston, Tom; Newberry, Jan
Highlights: Neighbourhood participation comprises both formal and informal modes of engagement. Formal neighbourhood participation can enhance residents' feeling of cohesion and belonging. Everyday neighbouring behaviours also help bolster a feeling of belonging and attachment. Community organizations have the potential to both encourage inclusion and exacerbate divisions. Abstract: Existing neighbourhood research suggests growing socio-spatial inequalities and decreased participation and social cohesion in cities across North America. This paper uses a multiple case study design and qualitative, in-depth interviews to explore individuals' experiences of participation in diverse neighbourhoods in Calgary, Alberta, Canada. Based on thematic analysis of interviews, it identifies four types of formal neighbourhood participation (stepping up, speaking out, addressing needs, and showing up) and six types of informal participation in which residents engaged (networking, caring, reciprocating, working together, watching out, and getting out). These empirical findings offer rich qualitative perspectives on neighbourhood social capital, also drawing attention to the intersectional factors and complex power dynamics that influence how residents participate in neighbourhoods and neighbouring behaviours. Overall, the paper highlights the potential for community-based organizations to foster more inclusive participation, while also shaping how place-based inequalities play out.